Pelatihan Implementasi Media Gambar Untuk Meningkatkan Kosakata Bahasa Inggris Sederhana di Kelas Vocabulary - Fitrah Yuliawati; Jaftiyatur Rohaniyah; Dinar Vincy Yunitaka B (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2026)
The objective of this community service activity was to enhance the ability of students—who are prospective teachers—to create visual teaching aids, specifically through drawing. The activity took place in the Vocabulary class at FKIP UIM Pamekasan, involving 29 students. The implementation followed a structured approach comprising socialization, training, mentoring, and evaluation phases. The results revealed that while the students possessed a talent for creating illustrative teaching aids, they often lacked the opportunity to put this skill into practice. The activity demonstrated the students' enthusiasm for producing visual aids for classroom instruction; throughout the mentoring process, they grew increasingly confident and creative in their work. Ultimately, the training and mentoring program for creating teaching aids was successfully conducted in the FKIP UIM Pamekasan Vocabulary class.